(untitled) (Research, Society and Development, 2022)
Objective: to investigate the scientific evidence about the contributions of nurses in care management aligned with patient safety in the operating room. Method: integrative review, carried out online in January 2021, in four databases in the Virtual Health Library, with the controlled descriptors “Management”, “Surgical Center”, “Patient Safety” and “Nurse”. Results: they were summarized in three categories Organization of work in the Surgical Center and Patient Safety; Surgical environment and risk factors to Patient Safety; Actions developed by nurses for safe care management. Conclusion: the management of surgical care requires knowledge of the characteristics of each surgical procedure, in addition to the articulated and engaged work of the multidisciplinary team. The safe surgery checklist is the most adopted tool and the nurse is one of the main responsible for its application.